A 90-day episode-of-care cost analysis of robotic-arm assisted total knee arthroplasty. (28th January 2019) - Cool, Christina L; Jacofsky, David J; Seeger, Kelly A; Sodhi, Nipun; Mont, Michael A
Aim: To evaluate 90-day episode-of-care (EOC) costs associated with robotic-arm assisted total knee arthroplasty (rTKA) versus manual TKA (mTKA).Patients & methods: TKA procedures were identified in Medicare 100% data. Accounting for baseline differences, propensity score matching was performed 1:5. 90-day EOC and index costs, lengths-of-stay, discharge disposition and readmission rates were assessed.Results:  A total of 519 rTKA and 2595 mTKA were included. Overall 90-day EOC costs were US$2391 less for rTKA (p < 0.0001). Over 90% of patients in both cohorts utilized post-acute services, with rTKA accruing fewer costs than mTKA. Post-acute savings can be attributed to discharge destination.Conclusion: rTKA incurred an overall lower 90-day EOC cost versus mTKA. Savings were driven by fewer readmissions and an economically beneficial discharge destinations.